Clinical, Electrophysiology, and Pathology Features of Dynamin Centronuclear Myopathy: A Case Report and Review of Literature. Issue 2 (December 2016) - Verma, Sumit; Balasubramanian, Suman B.
Abstract: Dynamin (DNM2) centronuclear myopathy (CNM) has variable age of onset, distal greater than proximal muscle weakness, ptosis with or without extraocular muscle weakness, and a characteristic muscle biopsy with radial sarcoplasmic strands giving spoke like appearance. The following case report highlights clinical, electrophysiology, and pathology features of a genetic confirmed DNM2 CNM subject. In addition, a review of literature on all genetic confirmed DNM2 CNM cases published in English literature from 2006 to 2016 is presented.